Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar Kelas XI Mata Pelajaran Produktif Teknik Kendaraan Ringan di SMK Teknologi Plus Padang - Aditya, Wandi; Martias, Martias (Lembaga Yasin AlSys, 2024)
This study aims to analyze the effect of problem-based learning (PBL) model on student learning outcomes in class XI Light Vehicle Engineering subjects at SMK Teknologi Plus Padang. The PBL model was chosen to increase students' activity, understanding, and interest in learning through contextual learning that can develop critical thinking skills. This study used quantitative methods with a Quasi Experiment design, involving 21 students in the experimental group and 21 students in the control group in the 2024/2025 school year. The Shapiro-Wilk normality test and Levene's homogeneity test showed that the pre-test and post-test data were normally distributed and homogeneous. The results of the independent sample t-test revealed a significant difference between the experimental group (average 77.90) and the control group (average 50.48) with a sig (2-tailed) value of 0.001 <0.05. These results indicate that the application of the PBL model can significantly improve student learning outcomes. The implications of this research provide evidence that problem-based learning models are effective in creating an active, collaborative, and meaningful learning environment, so they can be implemented in various learning contexts.